Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = x^2 - 5x + 4}[/tex]
[tex]\mathsf{x^2 - 5x + 4 = 0}[/tex]
[tex]\mathsf{x^2 - 5x + x - x + 4 = 0}[/tex]
[tex]\mathsf{x^2 - 4 - x + 4 = 0}[/tex]
[tex]\mathsf{x(x - 4) - 1(x - 4) = 0}[/tex]
[tex]\mathsf{(x - 1)(x - 4) = 0}[/tex]
[tex]\mathsf{f(x) = 2^{\:2x - 3}}[/tex]
[tex]\mathsf{f(4) = 2^{\:2(4) - 3}}[/tex]
[tex]\mathsf{f(4) = 2^{\:8 - 3}}[/tex]
[tex]\mathsf{f(4) = 2^{5}}[/tex]
[tex]\boxed{\boxed{\mathsf{f(4) = 32}}}\leftarrow\textsf{letra C}[/tex]